Relevansi Pemikiran Muhammad Baqir As-Sadr Mengenai Teori Produksi Dan Distribusi Di Era Modernisasi - Ramadhan, Fariz (Taraadin : Jurnal Ekonomi dan Bisnis Islam, 2025)
This research discusses the relevance of Muhammad Baqir As-Sadr's thoughts on production and distribution theory in the context of economic modernization. In an Islamic economic perspective, Baqir As-Sadr emphasizes the importance of supervision in production and distribution activities, and rejects the conventional view of limited resources. The focus on meeting people's needs and consumption principles according to Islamic law is in line with Indonesia's economic goals of realizing general prosperity. He pointed out that economic problems are not only related to the scarcity of natural resources, but also to human activities in managing them. Baqir As-Sadr's thoughts provide a valuable contribution in understanding and applying the theory of production and distribution in economic modernization, as well as providing direction for the development of studies or implementation of these concepts. Keyword : Production Theory, Distribution Theory, Muhammad Baqir As-Sadr